L’agrobiodiversité végétale au sein des paysages forestiers utilisés par les communautés Baka et Konabembé au Sud-Est Cameroun - Évariste Fongnzossie; Thomas Mbang Nkongo; Didier Dibong Siegfried; Marlene Ngansop (Revue d'ethnoécologie)
Agrobiodiversity plays an important role as a source of income, a lever for the resilience of agricultural systems to climate change, a reservoir of nutrients, a basis for various ecosystem services such as pollination, soil fertility, and regulation of water cycles. Despite this potential, it is currently experiencing significant threat of erosion. This work characterizes agro-biodiversity in forest landscapes used by the Konabembe and the Baka ethnic groups in South-East Cameroon and the implications for household food security. Ethnobotanical surveys were conducted in 42 households, including 17 Baka and 25 Konabembé, and floristic surveys based on presence-absence data were conducted to 161 farms. The study shows that food insecurity is a reality for both ethnic groups. It is, however, more marked among the Baka than the Konabembe. Floristic surveys allowed the identification of 170 species grouped in 61 families. Thirty four of them are cultivated crops mostly of Solanaceae family (9 espèces) and 136 are native forest species accompanying crops in farms, with a great richness of individuals of Sterculiaceae family. Manihot esculenta was the most frequent crop, while Musanga cecropioides was the native forest species most present in farms. Overall, 112 species (21 cultivated and 91 native forest species) form the common floristic pool of the Baka and Konabembé farms. This botanical community however masks some little differences. Nineteen species were present only in Konabembé farms. Although there is very little difference in terms of cultivated crops among the two ethnic groups, all species considered, Baka farms are floristically richer than those of Konabembé.Although these cultivated ecosystems contain a significant floristic diversity, this agrobiodiversity is still far from meeting the requirements of a balanced diet. Action is needed at various levels to promote sustainable agriculture practices that harness biodiversity conservation, sustainable land management, food security and resilience to the effects of climate change.